Preparative separation of alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols using silver nitrate-impregnated silica gel medium pressure liquid chromatography and analysis of sandalwood oil - Daramwar, Pankaj P.; Srivastava, Prabhakar Lal; Priyadarshini, Balaraman; Thulasiram, Hirekodathakallu V. (Analyst, 2012)
The major sesquiterpene constituents of East-Indian sandalwood oil (Z)-alpha- and (Z)-beta-santalols have shown to be responsible for most of the biological activities and organoleptic properties of sandalwood oil. The work reported here describes the strategic use of medium pressure liquid chromatography (MPLC) for the separation of both alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols. Silver nitrate impregnated silica gel was used as the stationary phase in MPLC for quantitative separation of alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols with mobile phases hexane and dichloromethane, respectively. The purities of alpha-santalene and (Z)-alpha-santalol obtained were >96%; however, beta-santalene and (Z)-beta-santalol were obtained with their respective inseparable epi-isomers. Limits of quantification (LoQ) relative to the FID detector were measured for important sesquiterpene alcohols of heartwood oil of S. album using serial dilutions of the standard stock solutions and demonstrated that the quality of the commercial sandalwood oil can be assessed for the content of individual sesquiterpene alcohols regulated by Australian Standard (AS2112-2003), International Organization for Standardization ISO 3518: 2002 (E) and European Union (E. U.).

Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol

Biocatalyst mediated regio- and stereo-selective hydroxylation and epoxidation of (Z)-alpha-santalol - Daramwar, Pankaj P.; Srivastava, Prabhakar Lal; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Organic & Biomolecular Chemistry, 2014)
Biocatalyst mediated regio- and stereo-selective hydroxylation and epoxidation on (Z)-alpha-santalol were achieved for the first time, using a fungal strain Mucor piriformis. Four novel metabolites were characterized as 10,11-cis-beta-epoxy-alpha-santalol, 5 alpha-hydroxy-(Z)-alpha-santalol, 10,11-dihydroxy-alpha-santalol and 5 alpha-hydroxy-10,11-cis-beta-epoxy-alpha-santalol. Using Amano PS lipase from Burkholderia cepacia, alpha- and beta-isomers of 10,11-cis-epoxy-alpha-santalol were resolved efficiently.

Functional characterization of novel sesquiterpene synthases from Indian sandalwood, santalum album - Srivastava, Prabhakar Lal; Daramwar, Pankaj P.; Krithika, Ramakrishnan; Pandreka, Avinash; Shankar, S. Shiva; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Indian Sandalwood, Santalum album L. is highly valued for its fragrant heartwood oil and is dominated by a blend of sesquiterpenes. Sesquiterpenes are formed through cyclization of farnesyl diphosphate (FPP), catalyzed by metal dependent terpene cyclases. This report describes the cloning and functional characterization of five genes, which encode two sesquisabinene synthases (SaSQS1, SaSQS2), bisabolene synthase (SaBS), santalene synthase (SaSS) and farnesyl diphosphate synthase (SaFDS) using the transcriptome sequencing of S. album. Using Illumina next generation sequencing, 33.32 million high quality raw reads were generated, which were assembled into 84,094 unigenes with an average length of 494.17 bp. Based on the transcriptome sequencing, five sesquiterpene synthases SaFDS, SaSQS1, SaSQS2, SaBS and SaSS involved in the biosynthesis of FPP, sesquisabinene, beta-bisabolene and santalenes, respectively, were cloned and functionally characterized. Novel sesquiterpene synthases (SaSQS1 and SaSQS2) were characterized as isoforms of sesquisabinene synthase with varying kinetic parameters and expression levels. Furthermore, the feasibility of microbial production of sesquisabinene from both the unigenes, SaSQS1 and SaSQS2 in non-optimized bacterial cell for the preparative scale production of sesquisabinene has been demonstrated. These results may pave the way for in vivo production of sandalwood sesquiterpenes in genetically tractable heterologous systems.